Hamas, Islam, and Israel - Spoerl, Joseph (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2006)
Abstract The electoral triumph of Hamas in the Palestinian elections of January 2006 has made it imperative for policy makers around the world to understand this group and its ideology. Is Hamas likely to soften its hostility to Israel? Is Hamas likely to receive significant support from the Muslim world? What are the odds that Hamas can be either placated or isolated? If Hamas can make a strong claim to be authentically Islamic in its ideological underpinnings, then it is more likely to receive support from portions of the Muslim world and less likely to be conciliatory vis-à-vis Israel. Unfortunately, a careful study of the ideology of Hamas and its parent, the Muslim Brotherhood, shows that that ideology is firmly rooted in traditional Islamic principles. Far from distorting or perverting classical Islamic law, Hamas and the Muslim Brotherhood can claim very plausibly that shari'a requires implacable and violent resistance to Israel, including terrorism, and denial of Israel's right to exist as a non-Muslim state located on Islamic territory. Efforts to placate or isolate Hamas are therefore unlikely to succeed.